EFFECTIVENESS OF ESSENTIAL OIL AS LARVACIDE ON Aedes aegypti - Sulistiyani, Asih (Majority, 2015)
Abstract Globally 1 million cases of Dengue Hemoragic Fever (DHF) reported to the World Health Organization every year with 20.000 deaths annually. It reached 65.000 cases in Indonesia with mortality rate 595 people in the period of 2011. In 2012 number of DHF cases in Lampung amounted to 68,44 per 100.000 population. Essential oils contain active components called terpenoids or terpenes may affect the process of secondary metabolism. Various studies of Aedes aegypti larvae fed by various plants extracts that contain essential oils, proven effective in killing larvae in 0,2% consentrasion until 1,2% concentration with 43% to 100% of the Aedes aegypti larvae death. The main mechanism of the larvacidal effects of essential oil is its active components interfere the nervous system, inhibit the growth of larvae and inhibit larva power to eat. Keywords : Aedes aegypti, DBD, essential oil, larvacide Abstrak Secara global 1 juta kasus dilaporkan pada World Health Organization setiap tahun, dengan 20 ribu kematian setiap tahunnya. Jumlah kasus DBD di Indonesia mencapai 65 ribu dengan kematian mencapai 595 jiwa pada periode tahun 2011. Angka kesakitan DBD di Provinsi Lampung tahun 2012 sebesar 68,44 per 100.000 penduduk. Minyak atsiri memiliki kandungan komponen aktif yang disebut terpenoid atau terpena dapat mempengaruhi suatu proses dari metabolisme sekunder. Berbagai penelitian terhadap larva Aedes aegypti yang diberi berbagai ekstrak tanaman yang mengandung minyak atsiri, terbukti efektif dalam membunuh larva pada rentang konsentrasi 0,2% sampai 1,2% dengan persentase rata-rata kematian larva uji Aedes aegypti sebesar 43% sampai 100%. Mekanisme utamanya adalah komponen aktif yang terdapat dalam minyak atsiri juga memiliki efek larvasida yaitu dengan cara mengganggu susunan saraf pada larva serta menghambat pertumbuhan larva dengan cara menghambat daya makan larva. Kata kunci : Aedes aegypti, DBD, larvasida minyak atsiri